Fusion and fission in the visual pathways - Kaposvári, P; Bognár, A; Csibri, P; Utassy, G; Sáry, Gy (Physiological research, 2014)
Inconsistent information from different modalities can be delusive for perception. This phenomenon can be observed with simultaneously presented inconsistent numbers of brief flashes and short tones. The conflict of bimodal information is reflected in double flash or fission, and flash fusion illusions, respectively. The temporal resolution of the vision system plays a fundamental role in the development of these illusions. As the parallel, dorsal and ventral pathways have different temporal resolution we presume that these pathways play different roles in the illusions. We used pathway-optimized stimuli to induce the illusions on separately driven visual streams. Our results show that both pathways support the double flash illusion, while the presence of the fusion illusion depends on the activated pathway. The dorsal pathway, which has better temporal resolution, does not support fusion, while the ventral pathway which has worse temporal resolution shows fusion strongly.
Keywords: sluchová percepce; Humans; Visual Pathways; zrakové korové centrum; Acoustic Stimulation; iluze; Female; Illusions; mladý dospělý; zraková percepce; Auditory Perception; lidé; Photic Stimulation; Visual Perception; světelná stimulace; časové faktory; Signal Detection, Psychological; ženské pohlaví; Male; Psychometrics; zrakové dráhy; Young Adult; mužské pohlaví; Visual Cortex; psychometrie; Time Factors; teorie detekce signálu; akustická stimulace